PENGARUH ECO LABEL DAN GREEN PRODUCT TERHADAP MINAT BELI - Purwanto, Nuri (2021)
The phenomenon that is currently developing is related to how people are able to meet their biological needs but can reduce the negative impact of the process of fulfilling these needs, especially on the environment, so that a movement returns to natural products, the method of explanation (explanatory research) is the method chosen in this study. The research was conducted with the consumer object of Ades AMDK users with a sample range of 100 respondents. The data collection method used to measure the eco label, green product and buying interest variables was done by distributing questionnaires or questionnaires given to respondents via google form, hypothesis testing using partial test (t) and determinant coefficient (R2). The data is processed using SPSS. After conducting a series of data analysis, it was found that the eco label and green product variables had an effect on consumer buying interest in Ades brand bottled drinking water, although it was found that in descriptive analysis all of these variables were in fairly good criteria,